The Effect of Organizational Culture, the Role of Internal Auditor and Auditor Integrity on Fraud Prevention - Falih Zaki Sudharma; Haliah; Nirwana (International Journal of Business and Applied Economics, 2023)
This research aims to determine the effect of organizational culture, the role of internal auditors and auditor integrity on fraud prevention at the Regional Inspectorate of South Sulawesi Province. The focus of this research is as many as 46 respondents.  The type of research conducted in this research is quantitative using primary data in the form of a questionnaire. The population of this research are auditors who are in the Regional Inspectorate of South Sulawesi Province. The method used to determine the sample is to use the census method. The analysis was carried out using the validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, partial test, coefficient of determination test and multiple regression analysis. The results of this research indicate that organizational culture has a positive and significant effect on fraud prevention, while the role of internal auditors and the integrity of the auditor has no and insignificant influence on fraud prevention.